عادات العقل وعلاقتها بالتفكير الابتكاري لدى طلاب المرحلة الثانوية بمدينة ترهونة - أبوستة آمال محمد سالم (Al-Qurtas, 2025)
عادات العقل وعلاقتها بالتفكير الابتكاري لدى طلاب المرحلة الثانوية بمدينة ترهونة